Synthesis of graphene oxide-TiO2 nanotubes-silver nanoparticles nanocomposite by gamma irradiation for antibacterial and post-harvest preservation purposes - Thi Phuong Anh, Nguyen; Thuy Loan, Pham Thi; Duy Khang, Nguyen Vu; Dang Khoa, Vo Nguyen (Vietnam Journal of Biotechnology, 2020)
In this study, graphene oxide (GO)-TiO2 nanotubes (TNTs)-silver nanoparticles (AgNPs) nanocomposites were synthesized under γ-ray irradiation at different doses (5, 10, 15, 20 and 25 kGy) from formerly synthesized GO, TNTs and AgNPs. They were then characterized by Fourier-transformed infrared (FTIR) and ultra-violet-visible (UV-Vis) spectroscopies, as well as by scanning electron (SEM) and transmission electron (TEM) microscopes. The spectral data indicated the assemblage of silver nanoparticles on both GO sheets and TiO2 nanotubes, as well as the assemblage of TiO2 nanotubes on GO sheets. In addition, their antibacterial activity against Escherichia coli and post-harvest preservation were investigated. Fresh bunches of green grapes were used for this study. AATCC 100-2012 and ISO 21527-1:2008 standards were used for all experiments. The obtained results indicated that all nanocomposite samples exhibited very high antibacterial activity against E. coli. Among which, the 20 kGy sample showed the highest value. Moreover, two samples (5 kGy and 25 kGy) possessed the lower number of yeasts and molds than that of control sample, indicating that the nanocomposites had partial contribution to the preservation of post-harvest crops. We have also found in this study that the dose range affected the antibacterial activity and preservation; and the highest dose range, however, was not always ideal for that purpose. With such fascinating properties, GO-TNTs-AgNPs will be the promising material for antibacterial and agricultural applications.